2015
DOI: 10.1002/pro.2737
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrinsic dynamics of cytochrome p450 proteins using normal mode analysis

Abstract: Cytochrome P450 enzymes are hemeproteins that catalyze the monooxygenation of a widerange of structurally diverse substrates of endogenous and exogenous origin. These heme monooxygenases receive electrons from NADH/NADPH via electron transfer proteins. The cytochrome P450 enzymes, which constitute a diverse superfamily of more than 8,700 proteins, share a common tertiary fold but < 25% sequence identity. Based on their electron transfer protein partner, cytochrome P450 proteins are classified into six broad cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
(149 reference statements)
0
12
0
Order By: Relevance
“…Students conducted quantitative analyses of sequence, structure, and dynamic similarities in Cytochrome P450 proteins and other enzymes involved in primary metabolic pathways to have in‐depth understanding of the structure‐dynamics‐function relationships in proteins. From the NMA study, students have demonstrated that differences in local fluctuations modulate substrate specificity and catalytic function of enzymes . The two end‐of‐semester projects, conducted in Fall 2013 and 2014, are described in Supporting Information Appendix VI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students conducted quantitative analyses of sequence, structure, and dynamic similarities in Cytochrome P450 proteins and other enzymes involved in primary metabolic pathways to have in‐depth understanding of the structure‐dynamics‐function relationships in proteins. From the NMA study, students have demonstrated that differences in local fluctuations modulate substrate specificity and catalytic function of enzymes . The two end‐of‐semester projects, conducted in Fall 2013 and 2014, are described in Supporting Information Appendix VI.…”
Section: Resultsmentioning
confidence: 99%
“…Protein dynamics and their impact on protein function have been the main focus of our research in the past several years [58,59,[61][62][63][64][65]. Several undergraduate researchers have collaborated in various projects dealing with fundamental questions on the role of protein motions in relation to their function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all CYP450s have a similar structural fold, they commonly have less than 20% sequence identities [ 51 ]. There are only three amino acid residues that are completely conserved (Cys in the CXG motif, and Glu and Arg in the motif) in the CYP450 superfamily proteins across almost all the biological kingdom species [ 34 , 52 ]. The amino acids “E” and “R” in the motif are occasionally reported as being non-conserved [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed mathematical description about normal mode analysis and how it is applicable to protein molecule is given in many studies [ 20 , [25] , [26] , [27] ]. NMA is a technique to study vibrational motion of harmonic oscillating system near the equilibrium state.…”
Section: Methodsmentioning
confidence: 99%